Analisis Tingkat Kesehatan Perusahaan Menggunakan Metode Earning dan Leverage Pada Perusahaan - Fikri Ahmad Fauzi; R. Deni Muhammad Danial; Dicky Jhoansyah (IPM2KPE, 2019)
This study aims to determine the method of earnings (profitability) and leverage (solvency) in measuring the level of company health at PT. Adhi Karya (Persero) Tbk and PT. Surya Semesta Internusa Tbk. This research uses quantitative descriptive analysis techniques. The results of this study indicate that it is known that there is one company that is in a healthy condition and one company in an unhealthy condition. Conclusion, companies that are in a healthy condition can better maintain the company's existing system of activities, and for companies that are not healthy, the company must quickly handle or immediately take an action regarding the system of company activities so that the company can be good and be in company condition healthy. Keywords: Company Soundness, Earning and Leverage Method